Confrontational but Respecting the Rules: The Minor Impact of the Finns Party on Legislative–Executive Relations. Issue 4 (12th March 2021) - Poyet, Corentin; Raunio, Tapio
Abstract: Having achieved a major breakthrough in the 2011 elections, the Finns Party remained in opposition but joined the governing coalition from 2015 until 2017 when the party suffered a serious internal split. This article shows that the overall impact of the populists on parliamentary procedures and culture has been modest. The Finns Party has adjusted to the strongly institutionalised parliamentary norms and it has not contested the existing patterns of legislative–executive relations. The populists have brought more confrontational elements to the debates but seem content operating within the established institutional constraints. Content analysis of oral and written questions shows the internal diversity of the party.